2015
DOI: 10.1002/jcp.25241
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches in Mitochondrial Dysfunction, Proteolysis, and Structural Alterations of Diaphragm and Gastrocnemius in Rats With Chronic Heart Failure

Abstract: Patients with chronic heart failure (CHF) experience exercise intolerance, fatigue and muscle wasting, which negatively influence their survival. We hypothesized that treatment with either the antioxidant N-acetyl cysteine (NAC) or the proteasome inhibitor bortezomib of rats with monocrotaline-induced CHF may restore inspiratory and limb muscle mass, function, and structure through several molecular mechanisms involved in protein breakdown and metabolism in the diaphragm and gastrocnemius. In these muscles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 79 publications
7
44
0
Order By: Relevance
“…Cachexia, characterized by severe body and muscle mass loss and systemic inflammation, negatively impacts the quality of life of the patients and is usually present in advanced stages of their disease. In animal models of cachexia and muscle wasting of different etiology (respiratory, cardiac and cancer-induced cachexia), similar features to those observed in patients have also been reported [611]. …”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…Cachexia, characterized by severe body and muscle mass loss and systemic inflammation, negatively impacts the quality of life of the patients and is usually present in advanced stages of their disease. In animal models of cachexia and muscle wasting of different etiology (respiratory, cardiac and cancer-induced cachexia), similar features to those observed in patients have also been reported [611]. …”
Section: Introductionsupporting
confidence: 64%
“…Recent evidence reported by our group and others [3, 4, 620] has shown that several cellular and molecular mechanisms are clearly involved in the pathophysiology of muscle mass loss in patients with muscle wasting [3, 4, 1620], as well as in different experimental models of cachexia [615]. The most relevant mechanisms are part of a cascade of events that lead to enhanced muscle protein breakdown [4, 16, 18], through several cellular signaling pathways [4, 16, 18], mitochondria respiratory chain dysfunction [6, 10, 14, 19, 2123], systemic inflammation [4, 5, 24], muscle and systemic oxidative stress [4, 6, 16, 2527], apoptosis [7], and autophagy [4, 28].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations